Utilizing the CHA₂DS₂-VASc-HSF Score to Predict Subclinical Acute Kidney Injury from Contrast Agents: A Focus on Neutrophil Gelatinase-Associated Lipocalin Biomarker : SCI-AKI and CHA₂DS₂-VASc-HSF Score - Masrul Syafri; Alles Firmansyah; Merlin Sari Mutma Indah; Yui Muya (CV. AKBAR PUTRA MANDIRI, 2025)
Background: Contrast-Induced Acute Kidney Injury (CI-AKI) is a common complication in patients undergoing Percutaneous Coronary Intervention (PCI), with Subclinical Contrast-Induced Acute Kidney Injury (SCI-AKI) detectable via biomarkers like Neutrophil Gelatinase-Associated Lipocalin (NGAL). The CHA₂DS₂-VASc score, developed for stroke risk in atrial fibrillation, has been modified to CHA₂DS₂-VASc-HSF for assessing cardiovascular risk, but its role in predicting SCI-AKI remains unclear. Objectives: This study aimed to evaluate the CHA₂DS₂-VASc-HSF score as an indicator for SCI-AKI risk in PCI patients, using NGAL as a biomarker for early kidney injury. Methods: A cohort study was conducted at Dr. M. Djamil General Hospital, Padang, from May to December 2024. Thirty-four patients with stable and unstable angina undergoing PCI were included. NGAL levels were measured before and after PCI. Statistical analysis examined the relationship between CHA₂DS₂-VASc-HSF score and SCI-AKI. Results: Nine patients (26.5%) were diagnosed with SCI-AKI. NGAL levels showed a significant difference between SCI-AKI positive and negative groups (p < 0.05), but no significant association was found between CHA₂DS₂-VASc-HSF score and SCI-AKI (p > 0.05). Discussion: The CHA₂DS₂-VASc-HSF score is effective for cardiovascular risk assessment but not for SCI-AKI prediction. SCI-AKI was better predicted by NGAL, a sensitive biomarker of early kidney injury. This study highlights the importance of combining multiple risk factors for accurate SCI-AKI risk stratification in PCI patients. Conclusion: The CHA₂DS₂-VASc-HSF score is not a reliable predictor for SCI-AKI. NGAL remains a valuable biomarker for early detection, emphasizing the need for a multifactorial approach in managing renal complications post-PCI.